Intravitreal Bevacizumab Injection Effect in Exudative Age Related Macular Degeneration - Gholamhossein Yaghoobi; Abbas Ataei Kachuei (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2016)
Exudative age-related macular degeneration is the most common cause of vision loss of people over the age 60 in the developed countries. The cause is not clear yet, but since Avastin is largely used for the treatment, therefore, this study was conducted to assess the influence of avastin. Methods: All the 76 patients with exudative age-related macular degeneration came under intravitreal bevacizumab injection by an ophthalmologist with 1/25 mg in 0/05 ml. The second and third injections were repeated one month after the first injection. Patients were followed up one week, one month,and then in the third and sixth months after treatment. All patients had eye examination including visual acuity, slit lamp assessment (Slit-Lamp), intra ocular pressure and fundus examination. Results: Visual acuity was 0/906±0/080 in patients before the study, a month after the injection 0/818 ± 0/097, and 3 months and 6 months after injection were 0/677± 0/126 and 0.488±0.164, respectively. The average difference in measured visual acuity was significant in all cases before injections, one month after injection, 3 months and 6 months after injection. (p<0.001). The only complication observed during this study was mild temporary anterior uveitis in two patients.(2/631%) Conclusion: Intravitreal injection of bevacizumab showed improvement in vision during this study within 6 months. The cost effectiveness of bevacizumab and no systemic side effect except for only two patients with mild temporary uveitis were the main finding.